MAKING LEARNING MORE ENJOYABLE: EVALUATION STRATEGIES AND INNOVATIVE IDEAS IN THE INDEPENDENT CURRICULUM OF HIGHER EDUCATION IN INDONESIA - QUALITATIVE STUDY - Agus Salim; Alim Hardiansyah; Nyi Dewi Puspitasari; Adi Mursalin; Eduard. L. Pesiwarissa (CV. ADIBA AISHA AMIRA, 2023)
This qualitative study aimed to explore evaluation strategies and innovative ideas to make learning more enjoyable in Indonesia's independent higher education curriculum. Data were collected through in-depth interviews with 20 lecturers and researchers and ten students from various faculties and analyzed using thematic analysis. The data collected from the in-depth interviews were analyzed using thematic analysis, which involved identifying patterns, themes, and categories in the data. The data were transcribed verbatim, and the transcripts were read and re- read several times to ensure the researchers thoroughly understood the data. The researchers then coded the data line by line, and these codes were grouped into categories based on their similarities and differences. The classes were then analyzed to identify themes, refined through an iterative discussion process and consensus among the researchers. The final pieces were then interpreted in the context of the research questions and the relevant literature. The findings reveal that lecturers and students acknowledge the importance of evaluation in improving learning outcomes and creating a positive learning experience. Lecturers use various evaluation strategies, such as self-assessment, peer, and formative assessments, to enhance students' engagement and motivation. Moreover, lecturers employ innovative ideas like gamification, multimedia, and project-based learning to make education more enjoyable. Students also perceive these creative ideas as effective ways to increase their motivation and enjoyment of learning.